Phytochemical Screening And Antidiabetic Test Of Ethanol Extract Of Turmeric Leaves (Curcuma domestica Val.) On Decreasing Blood Glucose Of Diabetic Rats - Br Turnip, Nur Ulina M; Harahap, Urip; Hasibuan, Poppy Anjelisa Z. (International Journal of Science, Technology & Management, 2023)
The turmeric plant (Curcuma domestica Val.) is a tropical plant that grows a lot on the Asian continent with is use as a food coloring and fragrance. The use of turmeric leaves by residents is only a cooking ingredient not used in large quantities. Even most of these turmeric leaves are considered waste and have minimal utilization. Turmeric leaf methanol extract can be used to lower blood glucose. Turmeric leaf extract has the potential as a valuable food source of its antioxidant components, such as total phenolic compounds and flavonoids which increase radical scavenging activity. In particular, the water extract of turmeric leaves contains high total phenolic compounds (2.741?±?0.099?mg GAE/g) and flavonoids (4.776?±?0.010?mg QCE/g). Diabetes mellitus is a metabolic disorder associated with several chronic complications, such as nephropathy, neuropathy, retinopathy and cardiomyopathy. Part of the turmeric plant leaves is reported to have the ability as an antioxidant. Antioxidant compounds can control blood glucose levels and prevent diabetes complications. This study was conducted to test the ability of turmeric leaf ethanol extract (EEDK) to reduce blood glucose levels in diabetic rats induced by nicotinamide and streptozotocin and to perform phytochemical screening to determine the compounds contained in turmeric leaves so that it becomes an alternative as a diabetes treatment and can prevent damage. or diabetic complications. The results showed that turmeric leaves contained secondary metabolites, namely flavonoids, glycosides, tannins, and triterpenoids/steroids, but there were no alkaloids or saponins. The characterization results show that the sample meets the requirements. Turmeric leaf ethanol extract doses of 400 mg/kg, 200 mg/kg, and 100 mg/kg could reduce the Blood Glucose Level of NA and STZ-induced rats from the fourth day of treatment.